Design and Rationale of the RE‐DUAL PCI Trial: A Prospective, Randomized, Phase 3b Study Comparing the Safety and Efficacy of Dual Antithrombotic Therapy With Dabigatran Etexilate Versus Warfarin Triple Therapy in Patients With Nonvalvular Atrial Fibrillation Who Have Undergone Percutaneous Coronary Intervention With Stenting. Issue 10 (26th August 2016) - Cannon, Christopher P.; Gropper, Savion; Bhatt, Deepak L.; Ellis, Stephen G.; Kimura, Takeshi; Lip, Gregory Y.H.; Steg, Ph. Gabriel; ten Berg, Jurriën M.; Manassie, Jenny; Kreuzer, Jörg; Blatchford, Jon; Massaro, Joseph M.; et al.
Abstract : Antithrombotic management of patients with atrial fibrillation (AF) undergoing coronary stenting is complicated by the need for anticoagulant therapy for stroke prevention and dual antiplatelet therapy for prevention of stent thrombosis and coronary events. Triple antithrombotic therapy, typically comprising warfarin, aspirin, and clopidogrel, is associated with a high risk of bleeding. A modest‐sized trial of oral anticoagulation with warfarin and clopidogrel without aspirin showed improvements in both bleeding and thrombotic events compared with triple therapy, but large trials are lacking. The RE‐DUAL PCI trial (NCT 02164864) is a phase 3b, a strategy of prospective, randomized, open‐label, blinded‐endpoint trial. The main objective is to evaluate dual antithrombotic therapy with dabigatran etexilate (110 or 150 mg twice daily) and a P2Y12 inhibitor (either clopidogrel or ticagrelor) compared with triple antithrombotic therapy with warfarin, a P2Y12 inhibitor (either clopidogrel or ticagrelor, and low‐dose aspirin (for 1 or 3 months, depending on stent type) in nonvalvular AF patients who have undergone percutaneous coronary intervention with stenting. The primary endpoint is time to first International Society of Thrombosis and Hemostasis major bleeding event or clinically relevant nonmajor bleeding event. Secondary endpoints are the composite of all cause death or thrombotic events (myocardial infarction, or stroke/systemic embolism) and unplanned revascularization; death or thrombotic events; individual outcome events; death, myocardial infarction, or stroke; and unplanned revascularization. A hierarchical procedure for multiple testing will be used. The plan is to randomize ∼ 2500 patients at approximately 550 centers worldwide to try to identify new treatment strategies for this patient population.